2023
DOI: 10.3390/pr11020438
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Cavitation Characteristics of a Centrifugal Pump Based on an Improved ZGB Model

Abstract: We modified the Zwart–Gerber–Belamri (ZGB) cavitation and RNG turbulence models based on their rotational motion characteristics, as well as simulating the phenomenon of small fluctuations in rotational speed due to the action of hydraulic excitation force, to increase the precision of numerical simulations of the cavitation characteristics of centrifugal pumps. According to the theory behind the enhanced model, the pressure gradient in the impeller runner changes uniformly, and the cavitation bubble initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Ranawat et al developed a test rig to explore blockage in pump, and long short term memory (LSTM) and Bi-directional long short term memory (Bi-LSTM) are used to evaluate performance [20]. The power spectral density and wavelet transform algorithm have been used to examine the cavitation noise characteristics in centrifugal pump [21]. Mishra et al investigated failure analysis of ball bearing in pump with envelope and demodulation techniques [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ranawat et al developed a test rig to explore blockage in pump, and long short term memory (LSTM) and Bi-directional long short term memory (Bi-LSTM) are used to evaluate performance [20]. The power spectral density and wavelet transform algorithm have been used to examine the cavitation noise characteristics in centrifugal pump [21]. Mishra et al investigated failure analysis of ball bearing in pump with envelope and demodulation techniques [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The predictions displayed that the best design was twisted, one having low to high twist pitches to obtain an average performance evaluation of about 2.03–2.71. Wang et al (2023) explored numerically the swirl flow transportation of a hydrate inside the passageway for various parameters of the twist tape through a discrete phase modeling and renormalization group (RNG) κ − ε turbulence model. Yu et al (2022) observed the turbulent thermal flow and took the heat transfer performance inside the oval tube with various twisted tapes in numerical work.…”
Section: Introductionmentioning
confidence: 99%